Percutaneous Coronary Intervention Strategy for Spontaneous Coronary Artery Dissection of Left Main Coronary Artery with Extensive Intramural Hematoma in the Main Side Branch - Makio Muraishi; Kosuke Maeda; Takuya Okada; Masahiko Noguchi (Case Reports in Cardiology)
A 46-year-old pregnant woman, presented with worsening episodes of intermittent chest pain. The patient was diagnosed with a non-ST-elevation myocardial infarction. On arrival, she had a stable hemodynamic status without chest pain. She was initially treated with conservative medical therapy. One day later, she complained of severe chest pain, and an electrocardiogram showed ST elevation in leads I, aVL, and V2-5. Emergency coronary angiography showed total occlusion of the left anterior descending artery (LAD) and intermediate stenosis of the left main coronary artery (LMCA). The intravascular ultrasound (IVUS) revealed an intramural hematoma (IMH) from the LMCA to the LAD, extending to the left circumflex artery (LCX) ostium. This finding was consistent with spontaneous coronary artery dissection (SCAD). After stent implantation from the LMCA to the LAD, severe stenosis was noted at the proximal site of the LCX. IVUS showed that the IMH extended to the LCX. The provisional crush stent technique was performed, and the final angiography revealed satisfactory results with thrombolysis in myocardial infarction flow grade 3 in the LAD and LCX. This case report highlighted that stent implantation in the SCAD lesions facilitated the extension of the IMH longitudinally and laterally into the side branch, resulting in stenosis or occlusion. Therefore, the side branch should be evaluated using IVUS before stent implantation. In cases where the IMH extends to the ostium of the side branch, two-stent techniques that do not require guidewire recrossing, such as crush stents, should be considered to avoid side branch occlusion.